2017
DOI: 10.1007/s11999-017-5310-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Based Hydrogel Coating Does Not Affect Bone Apposition at the Implant Surface in a Rabbit Model

Abstract: BackgroundUncemented orthopaedic implants rely on the bone-implant interface to provide stability, therefore it is essential that a coating does not interfere with the bone-forming processes occurring at the implant interface. In addition, local application of high concentrations of antibiotics for prophylaxis or treatment of infection may be toxic for osteoblasts and could impair bone growth.Questions/Purposes In this animal study, we investigated the effect of a commercially available hydrogel, either unload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
0
28
0
6
Order By: Relevance
“…Will the bioglass be in contact with the rabbit bone or will it be shielded? Authors: The empty hydrogel has proven to have no influence on bone apposition in a non-infected animal model with an implant (Boot et al, 2017). Although the bioglass is mixed with the hydrogel, it could be possible that the ions released from the bioglass are also released from the hydrogel; however, this was not tested.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
See 1 more Smart Citation
“…Will the bioglass be in contact with the rabbit bone or will it be shielded? Authors: The empty hydrogel has proven to have no influence on bone apposition in a non-infected animal model with an implant (Boot et al, 2017). Although the bioglass is mixed with the hydrogel, it could be possible that the ions released from the bioglass are also released from the hydrogel; however, this was not tested.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…Release studies showed that 2 % (w/v) vancomycin-loaded DAC ® releases over 80 % of the antibiotic within the first 24 h of in vitro incubation (Giavaresi et al, 2014), demonstrating that DAC ® can facilitate a fast delivery of the loaded agent. Furthermore, the hydrogel, when coated on titanium implants, has no effect on the volume or timing of bone growth near the implant and does not induce an inflammatory reaction in a rabbit implant-model (Boot et al, 2017). Also, the hydrogel loaded with antibiotics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…recent paper, focused on the impact on bone healing and implant osteointegration, reported no detrimental effects of vancomycin-loaded DAC ® or of DAC ® alone [57].…”
Section: Dac ® Hydrogel In Vivo Activitymentioning
confidence: 97%
“…This hydrogel engine was shown effective as a coating on titanium implants without inducing an inflammatory reaction. The idea was to develop an antibiotic‐loaded hydrogel loaded to offer a local protection for implants against bacteria without interfering with bone apposition or inducing a local or systemic inflammatory reaction . The versatility of hydrogels and the succeeded in vitro and in vivo outcomes makes it an interesting candidate to counteract implant‐related infections.…”
Section: Biomaterial‐based Solutions As Future Perspectives To Prevenmentioning
confidence: 99%